1964
DOI: 10.1677/joe.0.0290103
|View full text |Cite
|
Sign up to set email alerts
|

The Metabolism of Testosterone by Tissue From Normal and Neoplastic Rat Breast

Abstract: The qualitative and quantitative metabolism of testosterone by rat mammary gland and hydrocarbon-induced mammary tumours has been investigated. These tissues contain a \g=D\4-5\g=a\-hydrogenase, 3-ketosteroid reductase and 17 \g=b\-hydroxysteroiddehydrogenase. The qualitative picture was the same in all the tissues studied but a quantitative difference was evident. In general, the tumours metabolized more steroid than mammary gland tissue taken from animals in late pregnancy. No conversion of testosterone to o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
1

Year Published

1965
1965
1995
1995

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 13 publications
0
4
1
Order By: Relevance
“…Although no significant difference in steroid metabolism was detected between hormone-dependent and independent DMBA-induced rat mammary tumours (King et al, 1965) endocrine-treated animals were used and in the present study effects in such animals were more difficult to detect than in unmanipulated animals. Furthermore the levels of tumour 5ct reduction were at least 10-fold less (King et al, 1964) than those reported in the system used in the present study. It is possible that the apparent relationship detected in this study between hormone dependence and steroid metabolism is only causal and that some other feature of transplantation has caused the observed increase in testosterone metabolism.…”
Section: Tumour Growthcontrasting
confidence: 76%
“…Although no significant difference in steroid metabolism was detected between hormone-dependent and independent DMBA-induced rat mammary tumours (King et al, 1965) endocrine-treated animals were used and in the present study effects in such animals were more difficult to detect than in unmanipulated animals. Furthermore the levels of tumour 5ct reduction were at least 10-fold less (King et al, 1964) than those reported in the system used in the present study. It is possible that the apparent relationship detected in this study between hormone dependence and steroid metabolism is only causal and that some other feature of transplantation has caused the observed increase in testosterone metabolism.…”
Section: Tumour Growthcontrasting
confidence: 76%
“…Similar conversions are found in human breast cancer tissue [9]. Normal rat mammary gland and DMBA-induced mammary tumors have been shown in enzymatic assays to contain 17~-hydroxysteroid dehydrogenase, 3-ketosteroid reductase, and A4-5a-hydrogenase activities [29,35]. The enzymatic systems which process steroids in human breast cancer tissue are also present in DMBAinduced mammary tumors, thus supporting the use of DMBA-induced tumors as models of human breast cancer [4][5][6][7][8][9].…”
Section: Discussionmentioning
confidence: 62%
“…
HUMAN and rat mammary tumours metabolize steroid hormones and thus have the capacity to modify their local hormonal environment (Adams & Wong, 1968;Jones et al, 1970;King et al, 1964;Miller et al, 1974). In previous studies, we have investigated the metabolism of testosterone by a predominantly ovary-dependent DMBA-induced mammary tumour, and have shown it to be sensitive to levels of other hormones present in vitro (Miller, 1976a), or in vivo (Miller, 1976b, c;Buchan et al, 1976).
…”
mentioning
confidence: 99%